PRO-ENVIRONMENTAL BEHAVIOR AMONG BODY SHOP EMPLOYEES IN INDONESIA - Clara Moningka; Samantha June (Universitas Mercu Buana Jakarta, 2022)
Body Shop Indonesia is a company that upholds environmental values. These pro-environmental values are also applied in their organizational culture, including in existing regulations or policies. In this study, researchers are interested in describing the employee’s pro-environmental behavior who have instilled pro-environmental values. This research was conducted in industries that promote pro-environmental behavior. With a culture that focuses on environmental sustainability, the pro-environmental behavior of its employees will be more visible.Previous research was conducted in a particular area or organization in general. Measurement of pro-environmental behavior uses the Pro-Environmental Behavior (PEB) scale constructed by Blok, et al and adopted in the organizational context by Sanyal and Pal. The reliability of this scale is 0.810. Research on 150 employee respondents shows that they have a pro-environment that tends to be high. The results of this research can be used as a reference or basis for implementing a pro-environmental organizational culture